90 °C continuous-wave operation of GaInAsP/InP membrane distributed-reflector laser on Si substrate. (21st February 2017) - Hiratani, Takuo; Inoue, Daisuke; Tomiyasu, Takahiro; Fukuda, Kai; Amemiya, Tomohiro; Nishiyama, Nobuhiko; Arai, Shigehisa
Abstract: The temperature dependence of a GaInAsP/InP membrane distributed-reflector laser bonded on a Si substrate — which showed a low threshold current (0.29 mA) and a relatively high differential quantum efficiency (23% from the front side) at 20 °C — was measured. A characteristic temperature of the threshold current, T 0, of 84 K and a sub-mA threshold current operation up to 90 °C were obtained under a continuous-wave (CW) condition. Furthermore, single-mode operation up to 80 °C was also obtained.